Modulatory effects of isolated Lactobacillus paracasei from Malaysian water kefir grains on the intestinal barrier and gut microbiota in diabetic mice - Talib, Noorshafadzilah; Mohamad, Nurul Elyani; Chai, Ling Ho; Masarudin, Mas Jaffri (Springer, 2024)
Type 2 diabetes (T2DM) is one of the four major types of non-communicable diseases that have become a global health concern. Water kefir is a product of a brown sugar solution fermented with kefir grains which comprises around 30 microbial species in its grains. Water kefir possesses a wide range of health benefits, including anti-hyperlipidemic effects, and reduces hypertension and blood glucose levels in animal models. Reportedly, consuming water kefir containing probiotics may enhance the intestinal barrier and positively influence the composition of the intestinal microflora. The present study aimed to evaluate the regulatory effects of Lactobacillus paracasei isolated from Malaysian water kefir grains (MWKG) on the alterations of intestinal barrier and gut microbiota in diabetic mice via histopathological analysis of the distal colon and 16S rRNA gene sequencing on fecal microbiome. Results indicated that the administration of isolated Lactobacillus paracasei from MWKG to diabetic mice ameliorated the dominant probiotic phyla in the gut microbiota. Results showed that lower dose (LD) and high dose (HD) treatments of the isolated Lactobacillus paracasei could significantly reduce inflammatory cell infiltration in the distal colon of diabetic mice. The treatments revealed a significant decrease in the relative abundance of Firmicutes in the gut, 0.27 ± 0.06% for LD and 0.34 ± 0.04% for HD, compared to untreated (UN) diabetic mice, 0.40 ± 0.02%. These results suggest that L. paracasei isolated from MWKG could serve as a potential dietary supplement against intestinal inflammation and modify gut microbiota composition in patients with T2DM.